Strain-mediated coupling in a quantum dot-mechanical oscillator hybrid system - Yeo, I.; de Assis, P-L.; Gloppe, A.; Dupont-Ferrier, E.; Verlot, P.; Malik, N. S.; Dupuy, E.; Claudon, J.; Gérard, J-M.; Auffèves, A.; Nogues, G.; Seidelin, S.; et al. (Nature Nanotechnology, 2014)
Recent progress in nanotechnology has allowed the fabrication of new hybrid systems in which a single two-level system is coupled to a mechanical nanoresonator. In such systems the quantum nature of a macroscopic degree of freedom can be revealed and manipulated. This opens up appealing perspectives for quantum information technologies, and for the exploration of the quantum-classical boundary. Here we present the experimental realization of a monolithic solid-state hybrid system governed by material strain: a quantum dot is embedded within a nanowire that features discrete mechanical resonances corresponding to flexural vibration modes. Mechanical vibrations result in a time-varying strain field that modulates the quantum dot transition energy. This approach simultaneously offers a large light-extraction efficiency and a large exciton-phonon coupling strength g0. By means of optical and mechanical spectroscopy, we find that g0/2Ï€ is nearly as large as the mechanical frequency, a criterion that defines the ultrastrong coupling regime. Â© 2014 Macmillan Publishers Limited. All rights reserved.
Keywords: Physical Sciences - Quantum Mechanics